Counting Majorana bound states using complex momenta - Mandal, I. (Condensed Matter Physics, 2016)
Recently, the connection between Majorana fermions bound to the defects in arbitrary dimensions, and complex momentum roots of the vanishing determinant of the corresponding bulk Bogoliubov–de Gennes (BdG)
Hamiltonian, has been established (EPL, 2015, 110, 67005). Based on this understanding, a formula has been
proposed to count the number (n) of the zero energy Majorana bound states, which is related to the topological
phase of the system. In this paper, we provide a proof of the counting formula and we apply this formula to a
variety of 1d and 2d models belonging to the classes BDI, DIII and D. We show that we can successfully chart out
the topological phase diagrams. Studying these examples also enables us to explicitly observe the correspondence between these complex momentum solutions in the Fourier space, and the localized Majorana fermion
wavefunctions in the position space. Finally, we corroborate the fact that for systems with a chiral symmetry, these solutions are the so-called “exceptional points”, where two or more eigenvalues of the complexified
Hamiltonian coalesce. Нещодавно (EPL, 2015, 110, 67005) було встановлено зв’язок мiж фермiонами Майорани, зв’язаними з
дефектами у довiльнiй вимiрностi, i комплексними iмпульсними коренями детермiнанта вiдповiдного
об’ємного гамiльтонiану Боголюбова-де Жена. Базуючись на цьому розумiннi, запропоновано формулу
для пiдрахунку числа (n) зв’язаних станiв Майорани з нульовою енергiєю, якi пов’язанi з топологiчною
фазою системи. В цiй статтi дається вивiд формули пiдрахунку, яка застосовується до низки 1d i 2d моделей, що належать до класiв BDI, DIII i D. Показано, як можна успiшно побудувати топологiчнi фазовi
дiаграми. Вивчення даних прикладiв дозволяє явно спостерiгати вiдповiднiсть мiж цими комплексними
розв’язками для iмпульсу в Фур’є просторi i локалiзованими хвильовими функцiями фермiонiв Майорани
в позицiйному просторi. Накiнець, пiдтверджено факт, що для систем з хiральною симетрiєю цi розв’язки
є так званими “винятковими точками”, де два чи бiльше власних значень ускладненого гамiльтонiана
зливаються.